184 The presence of atrial fibrillation in acute myocardial infarction patients and hyperglycaemia. (8th December 2021) - Fabrizio, Michele; Paolisso, Pasquale; Bergamaschi, Luca; Angeli, Francesco; Toniolo, Sebastiano; Magnani, Ilenia; Donati, Francesco; Stefanizzi, Andrea; Sansonetti, Angelo; Armillotta, Matteo; Chiti, Chiara; Bartoli, Lorenzo; et al.
Abstract: Aims: In patients with acute myocardial infarction (AMI), hyperglycaemia is a common feature determining a worse prognosis. Few studies have examined the relationship between hyperglycemic status and atrial fibrillation in-hospital stay. To evaluate the relationship between admission hyperglycaemia (aHGL) and occurrence of atrial fibrillation (AF) in-hospital stay in patients with AMI, categorized as myocardial infarction with obstructive coronary artery disease (MIOCA) and myocardial infarction with nonobstructive coronary artery disease (MINOCA). Methods and results: Hyperglycaemia was defined as a serum glucose level ≥140 mg/dl at the time of hospital admission. AF was defined as a beat-to-beat variability in cycle length and morphology with irregular fibrillatory waves on surface ECG. Among 2702 patients (32.1% were female, mean age was 70.1 ± 13.4 years), 24.2% were diabetic. Out of 2702 patients, 2457 were MIOCA and 245 (9.1%) were MINOCA patients. At admission, the mean value of serum glucose levels was 146 ± 66 mg/dl. At hospital admission, hyperglycemic status was present in 37.7% of patients and 8.3% presented atrial fibrillation. At hospital admission, atrial fibrillation (aAF) was significantly frequent in hyperglycemic than normoglycaemic patients (11.5% vs. 6.3%, respectively; P < 0.001). In aHGL MIOCA patients had a higher rate of aAF (10.7%) than normoglycaemic MIOCA (6.4%; P < 0.001). In aHGL MINOCA patients had 31% aAF than normoglycaemic MINOCA patients (7.5%; P < 0.001). During the hospital stay, the new onset of atrial fibrillation was higher in aHGL than normoglycaemic status in total population (6.3% vs. 2.9%, P < 0.001), in MIOCA subgroup (6.3% vs. 3.1%, P < 0.001) and MINOCA subgroup (7.3% vs. 1.5%, P = 0.003). Multivariate analysis adjusted for age, sex, and diabetes revealed that the presence of hyperglycaemia was an independent predictor for the onset of atrial fibrillation (OR: 1.7; 95% CI: 1.1–2.6; P = 0.02). Conclusions: Hyperglycaemia was an independent predictor of new atrial fibrillation during hospitalization in patients with AMI. Moreover, at hospital admission, patients with hyperglycemic status presented a higher incidence of atrial fibrillation, both in MIOCA and MINOCA subgroups. Further studies are needed to understand the biological mechanisms involved in these associations.